Effect of Solution-Focused-Brief Counselling Technique on Procrastination Behaviour Among Primary School Teachers in Bauchi Metropolis - Garba, H.K.; Tanko, B.A. (Kashere Journal of Education, 2022)
This study determined the effect of Solution focused brief counselling technique on procrastination behaviour among primary school teachers in Bauchi metropolis, Bauchi State Nigeria. The study was guided by two research questions and hypotheses. A quasi-experimental design was used while all primary school teachers with procrastination behaviour in Bauchi metropolis were the population out which 27 teachers purposively selected were the sample for study. The Procrastination Scale developed by Lay (1986) with twenty (20) item questions was adapted by changing some items to suit present study. Items were mixed in the scale used as an instrument to avoid copy from each other for data collection; data collected were analyzed using t-test and analysis of covariance. Findings revealed that there is significant effect exist in the solution focused brief counselling technique on situational dimension procrastination behaviour among primary school teachers in Bauchi metropolis (t = 8.710. p=0.00). This implies that solution focus brief counselling technique is effective in reducing (situational dimension) procrastination behaviour among primary school teachers in Bauchi metropolis (7.417. p=0.00.). Among the recommendations given counsellors and psychologists should be trained and encouraged to use Solution focused; brief counselling technique to re-addressing primary school teachers with situational dimension or trait dimension of procrastination behaviour in Bauchi metropolis to enhance their teaching activities.